Robotics: Science and Systems IX 2013
DOI: 10.15607/rss.2013.ix.023
|View full text |Cite
|
Sign up to set email alerts
|

Sorry Dave, I'm Afraid I Can't Do That: Explaining Unachievable Robot Tasks Using Natural Language

Abstract: Abstract-This paper addresses the challenge of enabling nonexpert users to command robots to perform complex high-level tasks using natural language. It describes an integrated system that combines the power of formal methods with the accessibility of natural language, providing correct-by-construction controllers for high-level specifications that can be implemented, and easy-to-understand feedback to the user on those that cannot be achieved. This is among the first works to close this feedback loop, enablin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…Typically, when engineering robotics software, the missions are first expressed using natural-language requirements. These are then specified using domain-specific languages, many of which have been proposed over the last decades [12]- [14], [38]. These languages are often integrated with development environments that are used to generate code that can be executed within simulators or real robots [15]- [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, when engineering robotics software, the missions are first expressed using natural-language requirements. These are then specified using domain-specific languages, many of which have been proposed over the last decades [12]- [14], [38]. These languages are often integrated with development environments that are used to generate code that can be executed within simulators or real robots [15]- [17].…”
Section: Introductionmentioning
confidence: 99%
“…Conceptually, defining a robotic mission entails two problems. First, ambiguities in mission requirements that prevent precise and unambiguous specifications must be resolved [38], [42], [43]. Consider the very simple mission requirement "the robot shall visit the kitchen and the office."…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we present a corpus that is an order of magnitude larger, and apply the sequence-to-sequence framework that allows grounding to the full space of LTL formulae (instead of the GR(1) fragment). In an orthogonal direction, Raman et al [44] demonstrated the benefit of verifying LTL behavior by identifying unsatisfiable parts of LTL formulae and reporting which natural language commands resulted in these failures. Although verifiable behavior is a significant advantage of using LTL [23], we do not focus on verification in this work.…”
Section: Related Workmentioning
confidence: 99%
“…To allow users who may be unfamiliar with LTL to define specifications, some approaches such as that of [18] include a parser that automatically translates English sentences into LTL formulas. Many applications distinguish two primary types of properties allowed in a specification -safety properties, which guarantee that "something bad never happens", and liveness conditions, which state that "something good (eventually) happens".…”
Section: B Linear Temporal Logicmentioning
confidence: 99%